The Impact Of Academic Supervision On Improving The Quality Of Teaching In Schools - Dedi Sahputra (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research aims to analyze the impact of academic supervision on the quality of teaching in schools. This research uses a pre-test and post-test experimental design with an experimental group, where the teachers who are research subjects are given treatment in the form of academic supervision, then the quality of their teaching is measured before and after the treatment. The population of this study consisted of 59 teachers in the city of Jantho, all of whom were sampled using total sampling techniques. Data was collected through a questionnaire instrument filled out by teachers before and after academic supervision, which measured two main variables, namely academic supervision and teaching quality. To analyze the data, the Wilcoxon test was used because the data obtained was not normally distributed. The research results showed that there was a significant difference in the quality of teaching before and after academic supervision, with Asymp scores. Sig. (2-tailed) of 0,000. These findings indicate that academic supervision has proven effective in improving teacher teaching competence. This research suggests the need for continuous implementation of academic supervision to improve the quality of learning in schools. Keywords: academic supervision, teaching quality.